2014
DOI: 10.1002/2014jd022113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of simulated water balance from Noah, Noah‐MP, CLM, and VIC over CONUS using the NLDAS test bed

Abstract: This study assesses the hydrologic performance of four land surface models (LSMs) for the conterminous United States using the North American Land Data Assimilation System (NLDAS) test bed. The four LSMs are the baseline community Noah LSM (Noah, version 2.8), the Variable Infiltration Capacity (VIC, version 4.0.5) model, the substantially augmented Noah LSM with multiparameterization options (hence Noah-MP), and the Community Land Model version 4 (CLM4). All four models are driven by the same NLDAS-2 atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
139
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 85 publications
(125 reference statements)
11
139
1
1
Order By: Relevance
“…Consistent with prior research that has indicated the importance of atmosphere-surface interactions (Cai et al, 2014) and specifically soil moisture Seneviratne et al, 2010) in surface energy partitioning and thus near-surface T and q regimes and static energy, exclusion of SM from the ANN with three hidden layers (i.e., ANN-HL3) decreases model performance relative to ANN-HL3-SM and increases the RMSE for maximum θ e in 70 % of grid cells. The regions for which this impact is most strongly manifest are close to or within the "warming holes" described above and/or are located downstream of regions of significant county-level irrigation and anthropogenic enhancement of SM DeAngelis et al, 2010) (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Consistent with prior research that has indicated the importance of atmosphere-surface interactions (Cai et al, 2014) and specifically soil moisture Seneviratne et al, 2010) in surface energy partitioning and thus near-surface T and q regimes and static energy, exclusion of SM from the ANN with three hidden layers (i.e., ANN-HL3) decreases model performance relative to ANN-HL3-SM and increases the RMSE for maximum θ e in 70 % of grid cells. The regions for which this impact is most strongly manifest are close to or within the "warming holes" described above and/or are located downstream of regions of significant county-level irrigation and anthropogenic enhancement of SM DeAngelis et al, 2010) (Fig.…”
Section: Resultssupporting
confidence: 70%
“…Furthermore, we compare the performance of the CLM with Noah-MP (Niu et al, 2011), which serves as a participant model in Land Data Assimilation Systems (LDAS, Cai et al, 2014). Single-point Noah-MP simulations are conducted in the same way as CLM simulations to ensure their comparability.…”
Section: Model Simulationsmentioning
confidence: 99%
“…Generally, CLM-OL overestimated the SWC values for all sub-20 regions and in all seasons. This overestimation of soil moisture in CLM was also reported by Cai et al 2014 when compared with other land surface models and observations over Continental US. However, using data assimilation, this overestimation was reduced consistently in all sub-regions, as shown with CLM-DA.…”
Section: Resultsmentioning
confidence: 52%